2020
DOI: 10.1002/advs.201902802
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assembly of Nanoparticles Achieved through Synergy of Structure‐Based Protein Engineering and Synthetic DNA Generates Enhanced Adaptive Immunity

Abstract: Nanotechnologies are considered to be of growing importance to the vaccine field. Through decoration of immunogens on multivalent nanoparticles, designed nanovaccines can elicit improved humoral immunity. However, significant practical and monetary challenges in large‐scale production of nanovaccines have impeded their widespread clinical translation. Here, an alternative approach is illustrated integrating computational protein modeling and adaptive electroporation‐mediated synthetic DNA delivery, thus enabli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 70 publications
3
64
0
Order By: Relevance
“…We verified the engineered variant DLnano_CD4MutLS_GT8 incorporating the LS3-KO epitope could still assemble homogenously by expressing this new construct in vitro and performing size exclusion chromatography (SEC) of the lectin-column-purified DLnano_CD4MutLS_GT8 transfection supernatant. SEC showed CD4MutLS_GT8 assembled homogenously into 60-mer (single peak observed on the SEC trace centering at 12.33 mL retention volume) similar to what we previously observed for the wildtype eOD-GT8-60mer ( Figure 3 B) ( Xu et al., 2020 ). Additionally, Size Exclusion Chromatography Multi Angle Light Scattering (SEC-MALs) analysis determined the molecular weight of CD4MutLS_GT8 to be around 2 MDa, close to the observed molecular weight of eOD-GT8-60mer ( Figure S2 A) ( Xu et al., 2020 ).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…We verified the engineered variant DLnano_CD4MutLS_GT8 incorporating the LS3-KO epitope could still assemble homogenously by expressing this new construct in vitro and performing size exclusion chromatography (SEC) of the lectin-column-purified DLnano_CD4MutLS_GT8 transfection supernatant. SEC showed CD4MutLS_GT8 assembled homogenously into 60-mer (single peak observed on the SEC trace centering at 12.33 mL retention volume) similar to what we previously observed for the wildtype eOD-GT8-60mer ( Figure 3 B) ( Xu et al., 2020 ). Additionally, Size Exclusion Chromatography Multi Angle Light Scattering (SEC-MALs) analysis determined the molecular weight of CD4MutLS_GT8 to be around 2 MDa, close to the observed molecular weight of eOD-GT8-60mer ( Figure S2 A) ( Xu et al., 2020 ).…”
Section: Resultssupporting
confidence: 85%
“…We previously observed that scaffold domains used to drive in vivo assembly of nanoparticle vaccines could sometimes induce CD4+ T cell responses ( Xu et al., 2020 ). Here, we compared CD4+ T cell responses elicited by various nanoparticle scaffolding domains, ferritin from Helicobacter pylori (3BVE), LS from Aquifex aeolicus , and the viral cage of Prototype Foamy Virus (PfV), in BALB/c immunized with DNA-launched GT8 nanoparticle vaccines that incorporate these respective protein domains (DLnano_3BVE_GT8, DLnano_LS_GT8, DLnano_PfV_GT8) ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another demonstration, Xu et al reported the use of a DNA vaccine plasmid to induce the in vivo expression of a nanoparticle structural component comprising an HIV Env antigen fused with LS, and demonstrated its in vivo structural assembly in mice based on functional studies along with improved immune responses in mice and guinea pigs compared to immunization with a similar delivery strategy encoding antigen monomers only. [154] The design concept was further generalized to other natural protein scaffolds, such as ferritin nanoparticles, which also induced high immune responses and the delivery strategy could also be adapted to influenza HA antigen in order to endow mice with protective immunity against a lethal influenza virus challenge.…”
Section: (15 Of 25)mentioning
confidence: 99%